New Concept of Ignorance: An Islamic Epistemological Approach to The Story of Moses as Relevant Reference for Contemporary Ulama - D.I. Ansusa Putra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
The understanding of knowledge in the Islamic literature is more focus on the conception of knowledge itself, such as the epistemology of ma'rifah al-Ghazali, the epistemology of Islamic science Syed Nuqaib al-Attas, and the epistemology of the Qur’an Fazlur Rahman. This article is different from the previous concept that looks at knowledge from its antonym, Ignorance (Jahiliyyah). Ignorance is the important topic of socio-religious in the Qur’an which creates new understanding in Islamic epistemological construction. This article argues that in the Qur’an antonimical perspective, Ignorance is the antonym of the word